Natural products in atherosclerosis therapy by targeting PPARs: a review focusing on lipid metabolism and inflammation - Zhang, Yan; Zhang, Xue-Ying; Shi, Shan-Rui; Ma, Chao-Nan; Lin, Yun-Peng; Song, Wen-Gang; Guo, Shou-Dong (Frontiers in Cardiovascular Medicine, 2024)
Inflammation and dyslipidemia are critical inducing factors of atherosclerosis. Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors and control the expression of multiple genes that are involved in lipid metabolism and inflammatory responses. However, synthesized PPAR agonists exhibit contrary therapeutic effects and various side effects in atherosclerosis therapy. Natural products are structural diversity and have a good safety. Recent studies find that natural herbs and compounds exhibit attractive therapeutic effects on atherosclerosis by alleviating hyperlipidemia and inflammation through modulation of PPARs. Importantly, the preparation of natural products generally causes significantly lower environmental pollution compared to that of synthesized chemical compounds. Therefore, it is interesting to discover novel PPAR modulator and develop alternative strategies for atherosclerosis therapy based on natural herbs and compounds. This article reviews recent findings, mainly from the year of 2020 to present, about the roles of natural herbs and compounds in regulation of PPARs and their therapeutic effects on atherosclerosis. This article provides alternative strategies and theoretical basis for atherosclerosis therapy using natural herbs and compounds by targeting PPARs, and offers valuable information for researchers that are interested in developing novel PPAR modulators.